Dampak Pinjaman Online Dan Shopeepaylater Terhadap Pengelolaan Keuangan Pribadi Pengguna Di Kota Makassar - Nadiya Nur Fadilla; Wa Ode Rayyani (CV. ITTC INDONESIA, 2025)
This study aims to analyze the impact of using online loans and Shopee PayLater on users' personal financial management in Makassar City. These two digital financial services offer convenience and speed of access, which has attracted many individuals amidst urgent financial needs and shifting shopping habits to online platforms. Using a qualitative approach with phenomenological method, this research was located in Makassar City from June to July 2025. Data was collected through observation, semi-structured interviews, and documentation from six key informants selected through purposive sampling technique, who are active users of online loans or Shopee PayLater aged 20-40 years old. Data analysis involved reduction, presentation, and coding (open, axial, selective), followed by conclusion drawing. The results showed that the ease of access to online loans and Shopee PayLater significantly impacted users' debt management, spending arrangements, financial priorities, and consumptive behavior. The impact can vary, either worsening financial conditions through increased debt and consumptive behavior, or being a quick solution if used responsibly and supported by adequate financial literacy. This research emphasizes the importance of financial education to prevent unmanageable debt in the digital era.